TINGKAT KESUBURAN TANAH PADA AREAL EKS PENEBANGAN HUTAN DI AREAL HPH PT. KSK NANGA PINOH KAB. MELAWI - Siti Latifah; Ratna Herawatiningsih (Tengkawang : Jurnal Ilmu Kehutanan, 2018)
Forest harvesting is a logging activity, distribution of trunks, skidding, loading and transportation. This activity involves a lot of heavy equipment that results in soil compaction and reduced vegetation cover. This condition causes changes in soil fertility conditions. This study aims to determine changes in soil fertility that occur due to forest exploitation activities. Namely by observing the physical and chemical properties of the soil in the area of the former skid trail, ex-TPn, former TPk, former logging areas. The research method used for data retrieval is the survey method with porposive sampling, while the data obtained is analyzed using descriptive analysis. Based on the results of the analysis of the physical and chemical properties of the soil, it shows that the former TPN area is the area with the lowest soil fertility value. Former logging areas have the best quality of soil fertility compared to other areas; such as former skid trails, former TPk and former Tpn areas even though they are still included in the low fertility classification, with organic matter in the former logged area of 2.24%. The organic matter content is only 0.8% with clay texture.Keyword: harvesting, forest, forest land, soil fertility